Partially bio-based copolyesters poly(ethylene 2, 5-thiophenedicarboxylate-co-ethylene terephthalate): Synthesis and properties. (November 2020) - Wang, Guoqiang; Hao, Xingyu; Jiang, Min; Wang, Rui; Liang, Yin; Zhou, Guangyuan
Highlights: A series of bio-based copolyesters have been successfully synthesized from terephthalic acid (PTA), 2, 5-thiophenedicarboxylic acid (TDCA), and ethylene glycol (EG) by the melting polymerization. The effects of composition on microstructure, thermal properties, and mechanical properties were investigated. The esterification reaction time can be significantly reduced in the first step by the addition of TDCA because the acidity of TDCA is stronger than that of PTA. All polyesters exhibit high tensile strength (53.7–68.8 MPa) and good toughness (elongation at break: 190–508%). Compared with PET and PETTF25, PETTF49, PETTF74 and PETF show the lower processing temperature. Abstract: The aim of this study was to investigate the feasibility of replacing petroleum-based terephthalic acid (PTA) with renewable 2, 5-thiophenedicarboxylic acid (TDCA) in poly(ethylene terephthalate) ( PET), a series of copolyesters were synthesized from PTA, TDCA and ethylene glycol (EG). The effects of composition on structures, thermal properties, mechanical properties and β relaxation were studied. With the increase of the TDCA content, the esterification reaction time is noticeably shorter in the first step because the acidity of TDCA is stronger. PET, PETF and PETTF25 are semi-crystalline materials. However, no melting and crystallization peaks were observed for PETTF49 and PETTF74. All polyesters exhibit high tensile strength (56.0–68.8 MPa) and good toughness (elongation at break: 190–508%). With the increase of the TDCA content, β relaxation peak is shifted to a higher temperature. For all PET, PETF, and PETTFs, high peak intensity of the β relaxation can be achieved, indicating that the motions of more units are believed to contribute to the relaxation behavior.